Methanolysis of Carica papaya Seed Oil for Production of Biodiesel. (25th September 2014) - Agunbiade, Foluso O.; Adewole, Tolulope A.
Abstract : The future of fossil fuel sources of energy has necessitated the need to search for renewable alternatives. Thus, Carica papaya seed oil (CPSO) was employed as feedstock for the production of biodiesel by methanolysis. The seed was obtained locally, dried, and extracted with n-hexane. The CPSO was analyzed for specific gravity, viscosity, iodine value, and saponification value, among others using standard methods. The oil was transesterified by two-stage catalysis with oil to methanol mole ratio of 1 : 9. The biodiesel produced was subjected to standard fuel tests. The seed has an oil yield of 31.2% which is commercially viable. The kinematic viscosity of the oil at 313 K was 27.4 mm 2 s −1 while that of Carica papaya oil methylester (CPOME) was reduced to 3.57 mm 2 s −1 and the specific gravity was 0.84 comparable with other seed-oil biodiesels and number 2 diesel. Other oil properties were compared favourably with seed oils already documented for biodiesel synthesis. CPOME's cloud and pour points were 275 K and 274 K, respectively, and relatively higher than other biodiesels and number 2 diesel. CPOME exhibits moderate corrosion of copper strip. The methanolysis improved the fuel properties of the CPOME similar to other biodiesels. CPSO therefore exhibits a potential for biodiesel production.